The Injuries Caused by Electrical Currents - Aksoy, Mustafa Ercüment (The Bulletin of Legal Medicine, 1997)
Electric currents are used with increasing frequency as an energy source. The passage of electrical current through tissues can cause skin lesions, organ damage and death. The effects of electrical current are related to a number of factors which are the presence of a closed circuit, type of current, voltage, amperage, resistance of tissues, time and path of current. The mode of death in electrocution is ventricular fibrillation, spasm of respiretuar muscles, paralisy of respiration and cardiac centers and thermal burns. A through autopsy should be performed for an accurate diagnosis. The electrical lesions must be firstly investigated macroscopically, then histopathologicaly with a light microscope.There seems to be no universelly accepted pathognomonic microscobic features of an electrical lesion, but light microscobic examination is still the best convenient method. Further investigations are needed on this subject.Keywords: Electrical injuries, Wounds, Thermal lesions.
Keywords: electrical injuries; wounds; thermal lesions